Confronting self-discrepant events: Meaning-making and well-being in personal and political narratives. Issue 3 (3rd April 2021) - Meisels, Hannah Brier; Grysman, Azriel
ABSTRACT: The present study examined the relations among meaning-making, distress, well-being, and psychological growth in both personal and political self-discrepant narratives. Politically liberal participants (N = 159) narrated a self-discrepant experience and their reactions to the 2016 presidential election. Next, they completed measures assessing well-being, depressive and anxious symptoms, psychological growth, psychological functioning, and event centrality. Narratives were coded for meaning-making. In the political narratives, meaning-making partially mediated the relation between distress and well-being and this mediation was moderated by event centrality. Meaning-making mediated the relation between distress and psychological growth, regardless of event centrality. Results are considered in the context of how making meaning from distressing events buffers against their negative impact on the self.